2016
DOI: 10.1103/physrevx.6.041036
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Structures and Extreme Events in Rotating Multiphase Turbulent Flows

Abstract: International audienceBy using direct numerical simulations at unprecedented resolution we study turbulence under rotation in presence of simultaneous direct andinverse cascades. The accumulation of energy at large scale leads to the formation of vertical coherent regions with high vorticity oriented along the rotation axis. By seeding the flow with millions of inertial particles we quantify -for the first time- the effects of those coherent vertical structures on the preferential concentration of light and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 74 publications
6
91
0
Order By: Relevance
“…6(a)-6(b) and 6(g)-6(h)], which are very close to unity for k ⊥ 1/ρ i , regardless of the order m or of the threshold ξ. This is most likely a consequence of the pressure balance (6), which we studied in the preceding paragraphs. It is interesting to note that the ratios tend to converge towards the KAW predictions below the ion gyroradius rather then below the ion inertial scale.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…6(a)-6(b) and 6(g)-6(h)], which are very close to unity for k ⊥ 1/ρ i , regardless of the order m or of the threshold ξ. This is most likely a consequence of the pressure balance (6), which we studied in the preceding paragraphs. It is interesting to note that the ratios tend to converge towards the KAW predictions below the ion gyroradius rather then below the ion inertial scale.…”
Section: Resultsmentioning
confidence: 95%
“…Finally, we mention that the general approach employed here is not exclusively limited to kinetic range turbulence in astrophysical plasmas and we hope it might find exciting applications in a broad range of turbulent systems where waves and structures have been observed [5][6][7]20]. An immediate extension of the method lends itself in the context of inertial range plasma turbulence, where it could be used to study the interplay between structures and waves based on a generalized Alfvén ratio [19,96].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang and Domaradzki 42 , Müller and Thiele 43 , Mininni et al 44 , and Biferale et al 45 showed that the energy spectrum of rotating turbulence is approximately k −2 or k −2 ⊥ . However, Smith and Lee 46 and Sen et al 47 argued that the energy spectrum is proportional to k −3 ⊥ .…”
Section: Introductionmentioning
confidence: 99%